Investigating the roles of SMARCA4 and EP300 in synovial sarcoma - Doherty, Anthony (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2024)
Synovial sarcoma is a rare and aggressive cancer that accounts for approximately 10% of all soft tissue sarcomas diagnosed annually. This malignancy is caused by a characteristic fusion protein known as SS18- SSX and is particularly prevalent in adolescents and young adults. The disease-causing SS18-SSX fusion protein integrates into ATP-dependent chromatin remodelling SWI/SNF complexes; where it induces their redistribution along the chromatin fibre, driving oncogenic gene expression. Previous work from our lab and others has demonstrated that targeting SWI/SNF complexes in this disease using small molecules can yield significant therapeutic responses. Discoveries which have led to the initiation of clinical trials in synovial sarcoma patients. This PhD thesis aimed to extend our initial findings to examine additional opportunities to therapeutically target oncogenic SS18-SSX-containing SWI/SNF complexes. Firstly, publicly available DepMap CRISPR screening data was utilised to explore the genetic dependencies of all SWI/SNF subunits, aiming to identify novel vulnerabilities that exhibit a selective impact on synovial sarcoma cells. Through this approach, the catalytic SWI/SNF subunit SMARCA4 emerged as crucial in synovial sarcoma cell lines, with these cells displaying heightened sensitivity to SMARCA4 loss. Despite synovial sarcoma being traditionally consid- ered a classic SWI/SNF-perturbed cancer, comprehensive research into the functional role of SMARCA4 in this disease and the assessment of SMARCA4 targeting as a potential therapeutic strategy have not been addressed in published studies to date. Following on from the identification of SMARCA4 as a promis- ing genetic dependency in synovial sarcoma cells, the novel concept of complete protein degradation was embraced and utilised to characterise the biochemical consequences of SMARCA4 degradation. Secondly, having characterised the biochemical consequences of SMARCA4 degradation it was pertinent to examine the transcriptional effects of SMARCA4 loss and to examine the chromatin dynamics associated with SMARCA4 degradation. Addressing these key aims was important because mammalian SWI/SNF complexes are ATP- dependent chromatin remodelers that regulate DNA accessibility and control gene expression dynamics and SMARCA4/2 are the two mutually catalytic subunits found in all three SWI/SNF subclasses. In the ini- tial study from our lab which identified BRD9 as a critical functional dependency in synovial sarcoma, the E1A-binding protein p300 (EP300) was also identified as a promising therapeutic target in synovial sarcoma cells. The goal of the third research chapter was to follow up on this finding and to investigate the effect of perturbing EP300 function on the transcriptional program of synovial sarcoma cells.
APPROVED
Keywords: SMARCA4; SS18-SSX; Synovial sarcoma; EP300